Pengaruh Siklus Air Terhadap Kualitas Air Irigasi Pada Sistem Irigasi Pantai - Perpustakaan UGM, i-lib ([Yogyakarta] : Jur. Budidaya Pertanian Fak. Pertanian UGM, 1996)
The main problem of water management in the low lying paddy area is the affect of restricted drainage condition and is maintaining its water quality. Fresh water supply. from irrigation main canal and or from rainfall is required 10 manage the irrigation system. The management of this irrigation system is characterized by reuse of return flow. The conceptual definition of cyclic use of returning water, flow was' presented for evaluating the water use efficiency. ApplicatiOn of tank model (Kuroda et al, 1991) is very effective to explain the water reuse mechanism, fOr conserving irrigation water resources, thought it has very severe impact on water quality. By this concept the irrigation water could he oared from the upper block to the lower block in 2.5 days to 12.9 days. Surveying and analyzing of water quality such as p1-1, DO, SC, COD and T-Iï®1from the upper to the lower block were performed to know the effect of water conservation. From the result of the analysis it can be summerized that the water quality tend to decrease graduallyfrom the upper to the lower block because of the effect of water reuse mechanism